"Faba bean protein films reinforced with cellulose nanocrystals as edible food packaging material". (December 2021) - Rojas-Lema, Sandra; Nilsson, Klara; Trifol, Jon; Langton, Maud; Gomez-Caturla, Jaume; Balart, Rafael; Garcia-Garcia, Daniel; Moriana, Rosana
Abstract: In the present work, transparent films were obtained by the solution casting method from faba bean protein isolate (FBP), reinforced with different cellulose nanocrystals (CNCs) content (1, 3, 5 and 7 wt%), obtained by acid hydrolysis of pine cone, and using glycerol as plasticizer. The influence of different CNCs loadings on the mechanical, thermal, barrier, optical, and morphological properties was discussed. Microstructurally, the FTIR and FESEM results corroborated the formation of intramolecular interactions between the CNCs and proteins that lead to more compact and homogeneous films. These interactions had a positive influence on the mechanical strength properties, which is reflected in higher tensile strength and Young's modulus in reinforced films with respect to the control film, resulting in stiffer films as the CNCs content increases. Thermal stability of the FBP films was also improved with the presence of CNCs, by increasing the characteristic onset degradation temperature. In addition, the linkages formed between the CNCs, and proteins reduced the water affinity of the reinforced films, leading to a reduction in their moisture content and water solubility, and an increase in their water contact angle, obtaining more hydrophobic films as the CNCs content in the matrix increased. The addition of CNCs in the FBP film also considerably improved its barrier properties, reducing its water vapour transmission rate (WVTR) and oxygen transmission rate (OTR). The present work shows the possibility of obtaining biobased and biodegradable films of CNC-reinforced FBP with improved mechanical, thermal and barrier properties, and low water susceptibility, which can be of great interest in the food packaging sector as edible food packaging material. Graphical abstract: Image 1 Highlights: Faba beans protein films reinforced with different CNCs contents were studied. Addition of CNCs improved the strength properties of the Faba beans protein films. Faba beans protein films reinforced with CNCs showed improved barrier properties. Addition of CNCs decreases the water susceptibility of the Faba beans protein film.